Industrial leak testing of dangerous goods packagings. Issue 7 (15th April 2020) - Schlick‐Hasper, Eva; Neitsch, Marcel; Goedecke, Thomas
Abstract : The Dangerous Goods Regulations currently do not include limit leakage rates or sensitivity requirements for industrial leak testing procedures that are equivalent to the bubble test, which is the prescribed test method for design type testing of dangerous goods packagings. During series production of such packagings, various methods are used, which often do not meet the requirements of the bubble test with regard to important criteria. Sensitivity, flow direction, pressure level and automatability are particularly important factors when selecting a suitable industrial leak testing method. The following methods are in principle both suitable and equally effective as the bubble test: pressure rise test (vacuum chamber), ultrasonic bubble leak detection and gas detection methods (pressure technique by accumulation and vacuum chamber technique). To ensure a uniform test level during design type testing and production line leak testing and therefore a comparable safety level as required by the Dangerous Goods Regulations, it is necessary to include a more precise specification in these regulations. This requires, on the one hand, information about the sensitivity of the bubble test and, on the other hand, the inclusion of a list of suitable, equally effective industrial test methods with their specific boundary conditions. Abstract : The Dangerous Goods Regulations currently do not include limit leakage rates or sensitivity requirements for industrial leak testing procedures that are equivalent to the bubble test, which is the prescribed test method for design type testing of dangerous goods packagings. During series production of such packagings, various methods are used, which often do not meet the requirements of the bubble test with regard to important criteria. To ensure a uniform test level during design type testing and production line leak testing and therefore a comparable safety level as required by the Dangerous Goods Regulations, it is necessary to include a more precise specification in these regulations.